2004
DOI: 10.2465/jmps.99.225
|View full text |Cite
|
Sign up to set email alerts
|

Permo-Triassic ultrahigh-temperature metamorphism in the Kontum massif, central Vietnam

Abstract: The Kontum massif in central Vietnam consists of low grade schists and amphibolite to granulite facies metamorphic rocks, that have been intruded by S type and I type granites. This terrane was formerly considered to be composed mainly of Archean granulites (the Kannak Complex), Proterozoic amphibolite facies metamorphic rocks (the Ngoc Linh Complex) and low grade schists (the Kham Duc Complex). They were thought to be the basement of the Indochina Craton in south east Asia.The Kannak Complex is dominated by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 26 publications
3
54
0
2
Order By: Relevance
“…This age is consistent with the UHT metamorphism reported from the Kontum massif in the Indochina block (Nakano et al, , 2009Nam et al, 2001;Osanai et al, 2001Osanai et al, , 2004Owada et al, 2006Owada et al, , 2007. For instance, electron microprobe (EMP) dating of monazite showed that the timing of the metamorphism was ca.…”
Section: Ages Of the Granulite-facies Metamorphism And Granitic Magmasupporting
confidence: 77%
See 1 more Smart Citation
“…This age is consistent with the UHT metamorphism reported from the Kontum massif in the Indochina block (Nakano et al, , 2009Nam et al, 2001;Osanai et al, 2001Osanai et al, , 2004Owada et al, 2006Owada et al, , 2007. For instance, electron microprobe (EMP) dating of monazite showed that the timing of the metamorphism was ca.…”
Section: Ages Of the Granulite-facies Metamorphism And Granitic Magmasupporting
confidence: 77%
“…This event exerted a strong effect on both of the SCB and the Indochina block (Chen et al, 2011;Trung et al, 2006). In the Indochina block, the Kontum massif in central Vietnam experienced ultrahightemperature metamorphism in the late Permian (Nakano et al, , 2009Nam et al, 2001;Osanai et al, 2001Osanai et al, , 2004Owada et al, 2006Owada et al, , 2007. As a counterpart of the Kontum massif in the SCB (Chen et al, 2011), contemporaneous HT granulite-facies metamorphism occurred in the DSGB.…”
Section: Implications For Regional Crustal Evolutionmentioning
confidence: 99%
“…5; , Osanai et al, 2001b Grt Opx Cpx Ol Cpx Spl Opx Cpx Ol Grt Cpx Qz Omp Pgt Cpx Opx Pgt Amp Prg Hbl Bt , Tsunogae et al, 2000Tsunogae et al, , 2003aOsanai et al, 2016a Po Scp Schmetzer and Bank, 1983 Fig. 6 Table S1 , Ishizuka et al, 1998;Osanai et al, 1999aTsunogae and van Reenen, 2006 , Baba, 1998Baba, , 1999 , Tsunogae et al, 2011a 2 ;, Yoshimura et al, 2008;Kawasaki et al, 2011Baba et al, 2010Nakano et al, 2011Hokada et al, 2016, Sajeev et al, 2001Tsunogae and Santosh, 2003, Satish-Kumar et al, 2002Morimoto et al, 2004Koshimoto et al, 2004Shimizu et al, 2009Sajeev and Osanai, 2004a 3 ;, Osanai et al, 2001a;Nakano et al, 2004a , Osanai et al, 1998Osanai et al, , 2006a Table S1 , Hensen and Osanai, 1994;Das et al, 2001 , Sato et al, 2004;Kawasaki and Osanai, 2008 Motoyoshi, 2000;Osanai et al, 2004a;Sajeev and Osanai, 2004a Al Grt Cpx Grt Opx Spr Spl Fe-Mg Opx Cpx , Osanai et al, 1998;Tsunogae et al, 1999;Nakano et al, 2004a;Koshimoto et al, 2004;…”
Section: °C 1 Gpamentioning
confidence: 99%
“…1a and 1b). Both of these metamorphic rock types experienced a similar clockwise P-T evolution during the Late Permian and Early Triassic periods (270-240 Ma: Osanai et al, 2004;Nakano et al, 2004Nakano et al, , 2007aNakano et al, , 2007bNakano et al, , 2008Osanai et al, 2008;Nakano et al, 2009Nakano et al, , 2010. This led Osanai et al (2008) to propose the name 'Trans Vietnam Oro-genic Belt' (TVOB) for the region containing metamorphic and igneous rocks of this age ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrahigh-pressure (UHP) and/or ultrahigh-temperature (UHT) metamorphic rocks, together with syn-to post-collisional igneous rocks, are locally exposed in several collision zones in Asia (Okay et al, 1989;Ree et al, 1996;Zhang et al, 1996;Osanai et al, 2004;Oh et al, 2005;Osanai et al, 2008;Nakano et al, 2008Nakano et al, , 2010. Late Permian to Early Triassic continental growth in Asia can be accounted for by collage tectonics, exemplified by events such as the collisions between the South China and Indochina cratons, and the North China and South China cratons (Metcalfe, 1999;Ishiwatari and Tsujimori, 2003).…”
Section: Introductionmentioning
confidence: 99%